Rampant Caries in Stunted Children Aged 2-5 Years - Bunga Nurwati; Isnawati Isnawati; Sri Nuryati (Poltekkes Kemenkes Kupang, 2024)
The prevalence of stunting among children under five in the working area of Puskesmas (Community Health Centers) Karang Intan 2, based on data from the Banjar District Health Office in October 2022, was recorded at 506 cases. Dental and oral health issues, particularly dental caries, are among the most common health problems globally, affecting nearly half of the world's population or approximately 3.58 billion people. According to the 2018 Basic Health Research, dental caries, including decayed or damaged teeth, accounted for 45.3% of dental problems in Indonesia. This study aims to investigate rampant caries among stunted children aged 2–5 years in Pulau Nyiur Village, Karang Intan Subdistrict, Banjar District, South Kalimantan. The study employed a descriptive research design with a total sampling technique, involving 50 children aged 2–5 years attending the Posyandu within the working area of Puskesmas Karang Intan 2. The results revealed that male children outnumbered females in the sample. Among the participants, 36 children (72%) were stunted, while 14 children (28%) were not. The most common type of rampant caries was Type 3, affecting 15 children (31%), followed by Type 4 with 14 children (27%), Type 1 with 13 children (26%), and Type 2 as the least common, affecting 8 children (16%). It can be concluded that stunted children aged 2–5 years in Pulau Nyiur Village have a significant prevalence of rampant caries, with Type 3 being the most frequently observed. Additionally, the majority of stunted children in this study were male. These findings highlight the need for integrated interventions addressing both nutritional and dental health to reduce the prevalence of stunting and caries among young children.